A Hand Full of Numbers: A Role for Offloading in Arithmetics Learning? - Costa, Annelise J.; Silva, Júlia B.; Pinheiro-Chagas, Pedro; Krinzinger, Helga; Lonnemann, Jan; Willmes, Klaus; Wood, Guilherme; Haase, Vitor G. (Frontiers in Psychology, 2011)
Finger counting has been associated to arithmetic learning in children. We examined children with (n = 14) and without (n = 84) mathematics learning difficulties with ages between 8 to 11 years. Deficits in finger gnosia were found in association to mathematical difficulties. Finger gnosia is particularly relevant for the performance in word problems requiring active manipulation of small magnitudes in the range between 1 and 10. Moreover, the deficits in finger gnosia cannot be attributed to a shortage in working memory capacity but rather to a specific inability to use fingers to transiently represent magnitudes, tagging to be counted objects and reducing the cognitive load necessary to solve arithmetic problems. Since finger gnosia is more related to symbolic than to nonsymbolic magnitude processing, finger-related representation of magnitude seems to be an important link for learning the mapping of analog onto discrete symbolic magnitudes.